Faktor-Faktor Yang Berpengaruh Terhadap Praktik Merokok Pada Remaja Sekolah Menengah Pertama Di Kabupaten Kudus Tahun 2005 - Shaluhiyah, Zahroh; Karyono, Karyono; Noor, Farid (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2006)
Background : Smoking is a bad habit and harmful for health. Particularly when it is initiated in childhood period. People whose smoking is started in childhood have an increased chance of lung cancer compored with who start smoking later in life. Smoking behaviour was also predictive of heart diseases, stroke, blood vessel obstructions, impotent, miscorriage and so forth. In attempt to understand smoking behaviour among young people, this study has searched some factors that very influence to the smokingpractices among middle school students aged 11 – 15 years.Method : The researched involved 131 smoking student from 3 state middle schools and one private school which have been selected randomly. The study found that there were significant relationships between smoking practices of students and parental smoking,pochet money of student, level of socialization, knowledge and attitudes about smoking, parent child relationships and peer group smoking behaviour. The study also reveals that the most important factors for predicting smoking practice among students were parental smoking and attitudes of students, with report that student are threetimes as likely to smoke if their parents smoke and fourtimes as likely to smoke if they have positive attitudes to smoking.Result : Based on these fundings, the study recommended that in order to stop parental smoking, the government should established the programs of promoting smoking essation by using group motivation and social support in the implementing a restriction on smokingadvertising, banning smoking in public places. Where as the schools boards should establish the strict regulation in ganning smoking for students anywhere both in school and out of school.Keywords : smoking behaviour, young people, middle school students